Alterations of IL-6, IL-6R and gp130 in early and late onset severe preeclampsia. (August 2013) - Zhang, Zhan; Gao, Yan; Zhang, Linlin; Jia, Liting; Wang, Peng; Zhang, Lin; Li, He
Abstract : Objective: Interleukin-6 (IL-6) and its receptor complex participate in a number of critical biological activities through several signaling pathways. Placental dysfunction and increased inflammation are believed to underlie the pathogenesis of severe preeclampsia (PE), which may involve IL-6-induced signaling. We investigate whether the changes in the expression of IL-6 and its cognate receptors, IL-6 receptor (IL-6R) and glycoprotein (gp)130, occur between early and late onset severe PE. Methods: A total of 18 healthy gravidas and 41 severe preeclamptic women were recruited, including 20 pregnancies with early onset and 21 pregnancies with late onset. The IL-6, soluble IL-6R (sIL-6R) and soluble gp130 (sgp130) levels in maternal and umbilical cord sera were tested by enzyme-linked immunosorbent assay; the immunoactivities of IL-6, IL-6R and gp130 in the placentas were determined by immunohistochemistry and immunoblotting. Results: We found that (1) maternal serum IL-6 and sIL-6R levels were increased, whereas sgp130 was decreased in women with early onset severe PE compared with those with late onset severe PE and normal controls. In contrast to normal controls, IL-6 and sIL-6R expression was up-regulated in late onset severe PE, and similar alterations of IL-6 and its soluble receptors were detected in early and late onset severe PE umbilical sera and (2) compared with late onset severe PE, reduced IL-6 and IL-6R but not gp130 expression was observed in early onset severe PE placentas. Conclusion: These results suggest a probable contributing role of alterations in IL-6 and its corresponding receptors to the pathophysiology of early and late onset severe PE.